Level of Understanding and Implementation of PSAK 112 from The Waqf Accounting Perspective - Munzir Munzir; Lidya Aprilia Jumroh; Satria Lintang Rachmadana; Moh Ery Kusmiadi; Tri Rahmawati; Anggun Srimeilany Palamba; Nelwan Solossa; Asnat Way (www.amertainstitute.com, 2025)
Indonesia has a predominantly Muslim population so it has great potential in the development and management of waqf. Waqf is an Islamic financial instrument whose aim is for the benefit of the people, in accordance with Law No. 41 of 2004 which states that waqf is the legal act of a wakif to separate and/or hand over part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. The aim of the research was to determine the understanding of the Waqf Board of the Muhammadiyah Regional Leadership of Sorong Regency, Sorong City, South Sorong, and Raja Ampat Regency, and to find out how PSAK 112 was implemented in the Waqf Assembly of the Muhammadiyah Regional Leadership of Sorong Regency, Sorong City, and Raja Ampat Regency. The method used in this research is qualitative research with a phenomenological approach. This research was carried out at the Greater Sorong Muhammadiyah Regional Leadership Waqf and Land Council (Sorong Regency, Sorong City, and Raja Ampat Regency), Southwest Papua Province. The results of Nazir's research in understanding and implementing the PSAK 112 standard are that the PDM Waqf Council of Raja Ampat and South Sorong Regency does not yet understand PSAK 112. The second is the PDM Waqf Council of Sorong Regency and the PDM Waqf Council of Sorong City, which already understand and implement PSAK 112, as seen from the latest report on PSAK 112 and statements of interview results. This research means that waqf management institutions can report and present their financial reports according to PSAK 112 standards.